A comprehensive dual-spectroscopy detection technique based on TDLAS and QEPAS using a quartz tuning fork. (January 2022) - Wang, Zongliang; Tian, Cunwei; Qian, Siyu; Yu, Yuanfang; Chang, Jun; Zhang, Qinduan; Feng, Yiwen; Li, Hefu; Feng, Zhenbao
Highlights: A comprehensive dual-spectroscopy detection technique based on tunable diode laser absorption spectroscopy (TDLAS) and quartz enhanced photoacoustic spectroscopy (QEPAS) is demonstrated using a single quartz tuning fork (QTF) for signal detection. A QTF was used as a photodetector and an acoustic wave transducer to detect the TDLAS and QEPAS signal simultaneously for 2f signal enhancement. A gas absorption cell with 3 m optical path length was utilized to generate and enhance the TDALS signal. We tested the feasibility of the proposed dual-spectroscopy detection technique by detecting acetylene (C2 H2 ) at 1532.83 nm. The signal of the dual-spectroscopy technique was approximately 1.13 and 8.71 times higher than that of the QEPAS and TDLAS techniques based on QTF. The proposed dual-spectroscopy detection technique also showed superior gas sensing capability for trace gas detection and could achieve a minimum detection limit of 1.05 ppm. Abstract: A comprehensive dual-spectroscopy detection technique based on tunable diode laser absorption spectroscopy (TDLAS) and quartz enhanced photoacoustic spectroscopy (QEPAS) is demonstrated using a single quartz tuning fork (QTF) for signal detection. The QTF was utilized as an acoustic wave transducer for QEPAS signal detection. The QTF also served as a photoelectric detector for TDLAS signal detection based on the thermoelastic effect. The dual-spectroscopy detection structure was designed for TDLAS and QEPAS detection. The on-beam acoustic micro resonator (AMR) structure was placed on the upper end of the QTF for QEPAS signal enhancement, and the laser beam transmitted through the AMR was aligned to the QTF prong by an optical collimator for TDLAS signal detection. An absorption gas cell with an optical path length of 3 m was utilized in the TDLAS setup. The gas cell enhanced the absorption signal of the gas by virtue of its relatively long optical path. We tested the feasibility of the proposed dual-spectroscopy detection technique by detecting acetylene (C2 H2 ) at 1532.83 nm. The experimental show that the signal of the dual-spectroscopy detection technique is approximately 1.13 times that of the QEPAS signal. The proposed dual-spectroscopy detection technique also showed superior gas sensing capability for trace gas detection and could achieve a minimum detection limit of 1.05 ppm. The signal strength of the proposed dual-spectroscopy detection technique can be further enhanced by using an absorption gas cell with a longer optical path.